Differential regulation of CpG island methylation within divergent and unidirectional promoters in colorectal cancer. Issue 3 (2nd March 2019) - Namba, Shinichi; Sato, Kazuhito; Kojima, Shinya; Ueno, Toshihide; Yamamoto, Yoko; Tanaka, Yosuke; Inoue, Satoshi; Nagae, Genta; Iinuma, Hisae; Hazama, Shoichi; Ishihara, Soichiro; Aburatani, Hiroyuki; et al.
Abstract : The silencing of tumor suppressor genes by promoter CpG island (CGI) methylation is an important cause of oncogenesis. Silencing of MLH1 and BRCA1, two examples of oncogenic events, results from promoter CGI methylation. Interestingly, both MLH1 and BRCA1 have a divergent promoter, from which another gene on the opposite strand is also transcribed. Although studies have shown that divergent transcription is an important factor in transcriptional regulation, little is known about its implication in aberrant promoter methylation in cancer. In this study, we analyzed the methylation status of CGI in divergent promoters using a recently enriched transcriptome database. We measured the extent of CGI methylation in 119 colorectal cancer (CRC) clinical samples (65 microsatellite instability high [MSI‐H] CRC with CGI methylator phenotype, 28 MSI‐H CRC without CGI methylator phenotype and 26 microsatellite stable CRC) and 21 normal colorectal tissues using Infinium MethylationEPIC BeadChip. We found that CGI within divergent promoters are less frequently methylated than CGI within unidirectional promoters in normal cells. In the genome of CRC cells, CGI within unidirectional promoters are more vulnerable to aberrant methylation than CGI within divergent promoters. In addition, we identified three DNA sequence motifs that correlate with methylated CGI. We also showed that methylated CGI are associated with genes whose expression is low in normal cells. Thus, we here provide fundamental observations regarding the methylation of divergent promoters that are essential for the understanding of carcinogenesis and development of cancer prevention strategies. Abstract : In this study, we revealed that the extent of promoter methylation was different depending on the arrangement of genes using DNA methylation data of 119 colorectal cancer specimens. Divergent promoters were hypomethylated compared to unidirectional promoters. The provide data is essential for the understanding of the carcinogenic mechanism.